Estudio de factibilidad para la creacion de un camposanto privado en el canton Mocache, año 2015 - Rivera Douglas, Valeria Elisabeth (2016)
The present investigation work in question has as objective to design a study of feasibility for the creation of a Cemetery deprived in the canton Mocache. After seeing the necessary and important that is before for the inhabitants of the mentioned canton to have this service he/she has started the development of the present project that those people that want to offer another form of to honor and to remember to their dear beings by means of a new proposal will be directed that it is implanting. With the purpose of knowing if it is feasible the implementation of the Cemetery the Study of Market, Technical, Economic and Financial Analysis was made. Where it was identified that direct competition doesn't exist in the market when carrying out the analysis of the offer, because no company offers services of private burial, and the municipal cemetery is collapsed and without amplification possibilities for what enters to the market as an innovative product, what allows to establish new prices, with the analysis of the demand was determined through the surveys the welcome of the service in the market. The technical study allowed to establish the suitable place for the installation of the Cemetery, other important and necessary aspects that were considered for this study were the social reason, logo, slogan and the organizational structure with the one that will count the Cemetery, finally from the financial point of view we could say that the project is viable.